AUDIT REPORT LAG UNDER TIGHTENED REGULATIONS: EVIDENCE FROM INDONESIA’S CONSUMER NON-CYCLICALS - Handa, Adrian; Andreas, Andreas (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study examines the effects of operational complexity, management replacement, and firm size on audit report lag among consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2021–2023, following the implementation of Financial Services Authority Regulation (POJK) No. 14/POJK.04/2022, which introduced tighter reporting deadlines. Using a quantitative approach and 65 purposively selected firms, the results indicate that higher operational complexity and management replacement significantly increase audit report lag. Contrary to expectations, firm size shows a positive effect, suggesting that larger firms experience longer audit delays. This study contributes to the audit report lag literature by explaining the underlying audit mechanisms, including increased verification risk, coordination complexity, and information asymmetry under regulatory tightening. By focusing on the consumer non-cyclical sector—characterized by large operational scale, regulatory exposure, and stable public demand—the study extends Agency Theory by demonstrating that regulatory pressure may intensify, rather than reduce, agency conflicts. Practically, the findings highlight the importance of strengthening internal controls during managerial transitions, improving audit planning for complex clients, and adopting more context-sensitive regulatory enforcement to enhance reporting timeliness without exacerbating audit delays.